DETEKSI MOLEKULER Megalocytivirus PADA IKAN BUDIDAYA DENGAN METODE POLYMERASE CHAIN REACTION-RESTRICTION FRAGMENT LENGTH POLYMORPHISM - , LA ODE BAYTUL ABIDIN, S.Pi.; Dr. Ir. Murwantoko, M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Megalocytivirus was known as agents that caused serious systemic disease in freshwater and marine fishes. The mortality up to 100% and been reported in Indonesia. Megalocytivirus can be divided into three clusters i.e. infectious spleen and kidney necrosis virus (ISKNV), red sea bream iridovirus (RSIV), and turbot reddish body iridovirus (TRBIV). Because of clinical symptoms and pathology of those Megalocytiviruses were similar, the molecular detection methods were needed to distinguish the clusters. In this research we used polymerase chain reaction-restriction fragment length polymorphism (PCR- RFLP) to detect Megalocytivirus and distinguish between clusters ISKNV and RSIV from cultured fishes in Indonesia. A primer pair was designed base on the conserved sequences of ORF 120R-121L from ISKNV and the homologous sequences from other Megalocytivirus. The DNA collection and DNA which extracted from tissue and fish samples were used as templates to amplify a fragment DNA of Megalocytivirus. The amplified DNA sequences were digested using EcoRV to determine the cluster. The four DNA amplicon of Megalocytivirus represent the sampling area were sequenced. In this research we successfully designed primers which able to detect Megalocytivirus by producing 729 bp DNA fragment. Among 51 samples, we found that 13 isolates from marine and freshwater fishes which originally from Purwokerto, Gondol, Karimunjawa and Situbondo were positive infected by Megalocytivirus. Digestion using EcoRV enzyme showed that all isolates were belonged into ISKNV cluster. Sequences analysis showed that those isolates shared 99,45-99,86% similarity on nucleotide level with ISKNV reference.